Daily dynamics of contrasting spring algal blooms in Santa Monica Bay (central Southern California Bight). (26th July 2022) - Ollison, Gerid A.; Hu, Sarah K.; Hopper, Julie V.; Stewart, Brittany P.; Smith, Jayme; Beatty, Jennifer L.; Rink, Laura K.; Caron, David A.
Abstract: Protistan algae (phytoplankton) dominate coastal upwelling ecosystems where they form massive blooms that support the world's most important fisheries and constitute an important sink for atmospheric CO2 . Bloom initiation is well understood, but the biotic and abiotic forces that shape short‐term dynamics in community composition are still poorly characterized. Here, high‐frequency (daily) changes in relative abundance dynamics of the metabolically active protistan community were followed via expressed 18S V4 rRNA genes (RNA) throughout two algal blooms during the spring of 2018 and 2019 in Santa Monica Bay (central Southern California Bight). A diatom bloom formed after wind‐driven, nutrient upwelling events in both years, but different taxa dominated each year. Whereas diatoms bloomed following elevated nutrients and declined after depletion each year, a massive dinoflagellate bloom manifested under relatively low inorganic nitrogen conditions following diatom bloom senescence in 2019 but not 2018. Network analysis revealed associations between diatoms and cercozoan putative parasitic taxa and syndinean parasites during 2019 that may have influenced the demise of the diatoms, and the transition to a dinoflagellate‐dominated bloom.